PENGARUH PERSONALITY, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR SERTA DAMPAKNYA TERHADAP KINERJA GURU PADA SEKOLAH MENENGAH DI KECAMATAN INDRA MAKMUR KABUPATEN ACEH TIMUR - Satria, Puji; Matriadi, Faisal; Maryudi, Maryudi (J-MIND (Jurnal Manajemen Indonesia), 2020)
ABSTRACTThe purpose of this study was to determine and analyze the influence of personality, organizational culture and organizational commitment on organizational citizenship behavior and teacher performance in high schools in Indra Makmur District, North Aceh Regency. The number of samples in this study were 126 teachers obtained by saturated sample technique. The data analysis method used was Structural Equation Modeling (SEM) using AMOS 21 software. The results of this study found that directly, personality and organizational culture had a positive and significant effect on organizational citizenship behavior, while organizational culture has no significant effect. Furthermore, the results of the study found that personality and organizational citizenship behavior had a positive effect on teacher performance, but organizational culture had a negative effect and organizational commitment had no significant effect. The results of the mediation effect test found that organizational citizenship behavior is able to fully mediate the influence of organizational culture and personality on performance, but not to be a mediator on the effect of organizational commitment on theacher performance.Keywords      :    Personality, Organizational Culture, Organizational Commintment, Organizational Citizenship Behavior and Theacher Performance